Diversity of variant alleles encoding Kidd, Duffy, and Kell antigens in individuals with sickle cell disease using whole genome sequencing data from the NHLBI TOPMed Program. Issue 2 (24th November 2020) - Dinardo, Carla L.; Oliveira, Theo G. M.; Kelly, Shannon; Ashley‐Koch, Allison; Telen, Marilyn; Schmidt, Luciana C.; Castilho, Shirley; Melo, Karla; Dezan, Marcia R.; Wheeler, Marsha M.; Johnsen, Jill M.; Nickerson, Deborah A.; et al.
Abstract: Background: Genetic variants in the SLC14A1, ACKR1, and KEL genes, which encode Kidd, Duffy, and Kell red blood cell antigens, respectively, may result in weakened expression of antigens or a null phenotype. These variants are of particular interest to individuals with sickle cell disease (SCD), who frequently undergo chronic transfusion therapy with antigen‐matched units. The goal was to describe the diversity and the frequency of variants in SLC14A1, ACKR1, and KEL genes among individuals with SCD using whole genome sequencing (WGS) data. Study Design and Methods: Two large SCD cohorts were studied: the Recipient Epidemiology and Donor Evaluation Study III (REDS‐III) (n = 2634) and the Outcome Modifying Gene in SCD (OMG) (n = 640). Most of the studied individuals were of mixed origin. WGS was performed as part of the National Heart, Lung, and Blood Institute's Trans‐Omics for Precision Medicine (TOPMed) program. Results: In SLC14A1, variants included four encoding a weak Jk a phenotype and five null alleles ( JK null ). JKA*01N.09 was the most common JK null . One possible JK null mutation was novel: c.812G>T. In ACKR1, identified variants included two that predicted Fy x ( FY*X ) and one corresponding to the c.‐67T>C GATA mutation. The c.‐67T>C mutation was associated with FY*A ( FY*01N.01 ) in four participants. FY*X was identified in 49 individuals. In KEL, identified variants included three null alleles ( KEL*02N.17, KEL*02N.26, and KEL*02N.04 ) and one allele predicting Kmod phenotype, all in heterozygosity. Conclusions: We described the diversity and distribution of SLC14A1, ACKR1, and KEL variants in two large SCD cohorts, comprising mostly individuals of mixed ancestry. This information may be useful for planning the transfusion support of patients with SCD.